Evaluación de la adulteración de leche con lactosuero por la técnica analítica: espectroscopía del infrarrojo con transformada de fourier en la región media (FT-MIRS) y cercana (FT-NIRS) (2019)
The adulteration of milk with whey is a problem that has boomed in recent years. In the process of making cheese by enzymatic action, between 70 to 80% of the total milk used is transformed into whey. This by-product of slightly acidic character reaches up to 50% of the original nutrients of the milk (vitamins, proteins, fats, carbohydrates), however, in Colombia it is not processed, so its disposition is not regulated, causing it to be used as an agent to dilute the milk, taking advantage of its compositional similarities and the inability of traditional physical-chemical methods to detect it, generating profit from a practice that Colombian law prohibits.